Estimation of future hydropower generation of reservoir systems used for different purposes in different regions - Kilic, Murat (IET renewable power generation, 2024)
In recent years, growth in environmental awareness and increasing non‐renewable energy costs have augmented the interest in hydropower generation as a renewable energy. The volume of water stored in a reservoir system is crucial in hydropower production and has deep uncertainty. The subject of this investigation is the estimation of the amount of future hydropower generation in reservoir systems, some of which have multi‐purpose use. This investigation was carried out in Turkey at Atatürk, Keban, Karakaya and Demirköprü Dams. In the estimation of the hydropower generation for future, the decision matrices were devised and run separately for each reservoir system. In the verification of the validity of the model, the amounts of energy generated in reality in the last three years, which were not included in the modelling process, were used for the reservoirs investigated. In the verification process, when the model results and the amounts of energy produced in reality are compared, similar satisfactory results were obtained which are compatible with the properties of the regions where the reservoirs were built. It is expected that the proposed model will provide a decision support tool especially in multi‐objective planning of constrained water resources.